2019
DOI: 10.1136/bmjgh-2018-001285
|View full text |Cite
|
Sign up to set email alerts
|

‘Management of a spoiled identity’: systematic review of interventions to address self-stigma among people living with and affected by HIV

Abstract: BackgroundSelf-stigma, also known as internalised stigma, is a global public health threat because it keeps people from accessing HIV and other health services. By hampering HIV testing, treatment and prevention, self-stigma can compromise the sustainability of health interventions and have serious epidemiological consequences. This review synthesised existing evidence of interventions aiming to reduce self-stigma experienced by people living with HIV and key populations affected by HIV in low-income and middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 83 publications
1
113
0
Order By: Relevance
“…was the significant decrease in internalized stigma experienced by intervention arm participants across all study sites. AYA are in a developmental stage when they are "developing and consolidating their sense of self" [45], and the impact of internalized stigma among this age group is not well studied [46]. In a systematic review of stigmareduction interventions in low-and middle-income countries, the authors found only one study that focused on youth [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was the significant decrease in internalized stigma experienced by intervention arm participants across all study sites. AYA are in a developmental stage when they are "developing and consolidating their sense of self" [45], and the impact of internalized stigma among this age group is not well studied [46]. In a systematic review of stigmareduction interventions in low-and middle-income countries, the authors found only one study that focused on youth [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…AYA are in a developmental stage when they are "developing and consolidating their sense of self" [45], and the impact of internalized stigma among this age group is not well studied [46]. In a systematic review of stigmareduction interventions in low-and middle-income countries, the authors found only one study that focused on youth [46,47]. This study used motivational interviewing to change sexual risk behaviors and alcohol use among Thai youth and did not find evidence of an impact on internalized stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma interventions have been reviewed extensively but have focused on enacted stigma (Siegfried & Beanland, 2017;Stangl et al, 2013) rather than self-stigma. Self-stigma or internalised stigma, although defined by Goffman decades ago (1963), remains strikingly understudied (Pantelic et al, 2019). In our research, self-stigma was a rising concern regarding HIV testing uptake and treatment, and was described as an even stronger barrier to HIV testing and treatment than enacted stigma.…”
Section: Discussionmentioning
confidence: 52%
“…Our findings further suggest that early intervention in the form of psychological support might help improve retention in care amongst young people who have experienced various forms of discrimination. Little is known about what might work to address internalized stigma among young people living with HIV but the broader, adult‐focused evidence base points to cognitive behavioural therapy, economic strengthening and community mobilization as promising approaches [46]. These should be adapted and tested for use among adolescents living with HIV.…”
Section: Discussionmentioning
confidence: 99%